FILM AVATAR DAN CERMINAN DUNIA VIRTUAL - Mafar, Fiqru (Universitas Lancang Kuning, 2013)
The virtual world has rised the three understanding oflife, that is destopian, neofuturist, and teknorealist. In this writing, the lvriterwill present a reflection of virtual world featured in a film entitles Avatar by James Cameron. This study uses a qualitative method by observing the scenes featured in the film. Tiris research f01.md that the virtual world featured in Avatar belongs to the understanding teknorealist. It can be seen from the representation of reality, identity, community, and the space displayed.